Avoiding Diagnostic Lens Fogging During the COVID-19 Era - Pérez González D (Dove Medical Press, 2020)
David Pérez González,1 Anat Loewenstein,1 Dan D Gaton2 1Department of Ophthalmology, Tel Aviv Sourasky Medical Center, Sackler Faculty of Medicine, Tel Aviv, Israel; 2Department of Ophthalmology, Rabin Medical Center, Sackler Faculty of Medicine, Tel Aviv, IsraelCorrespondence: David Pérez GonzálezDepartment of Ophthalmology, Tel Aviv Sourasky Medical Center, Sackler Faculty of Medicine, Weizmann Street #6, Tel Aviv 6423906, IsraelTel +972 -58-767-8471Email davidperezgonzalez90@gmail.comAbstract: Since the advent of COVID-19, the patient’s use of a face mask hampers our visibility because there is a marked fogging in our view produced by the warm breath that escapes from the top of the patient’s mask and lands on the cooler surface of the lens. This panorama is sometimes so frustrating that we have been forced to ask our patients to remove their facemasks while examined, increasing the risk of being infected. We consider it essential to share this small pearl technique that we can apply in order to avoid fogging during the examination; it is easy, and most importantly, without putting at risk the patient or doctor’s health. In our opinion, this is the first material to propose this technique.Keywords: technique, diagnosis, ophthalmology, enhancement, clarity